Caregiver sensitivity predicts infant language use, and infant language complexity predicts caregiver language complexity, in the context of possible emerging autism. Issue 4 (23rd December 2022) - Smith, Jodie; Chetcuti, Lacey; Kennedy, Lyndel; Varcin, Kandice J.; Slonims, Vicky; Bent, Catherine A.; Green, Jonathan; Iacono, Teresa; Pillar, Sarah; Taylor, Carol; Wan, Ming Wai; Whitehouse, Andrew J. O.; et al.
Abstract: While theory supports bidirectional effects between caregiver sensitivity and language use, and infant language acquisition—both caregiver‐to‐infant and also infant‐to‐caregiver effects—empirical research has chiefly explored the former unidirectional path. In the context of infants showing early signs of autism, we investigated prospective bidirectional associations with 6‐min free‐play interaction samples collected for 103 caregivers and their infants (mean age 12‐months; and followed up 6‐months later). We anticipated that measures of caregiver sensitivity/language input and infant language would show within‐domain temporal stability/continuity, but also that there would be predictive associations from earlier caregiver input to subsequent child language, and vice versa. Caregiver sensitive responsiveness (from the Manchester Assessment of Caregiver–Infant interaction [MACI]) predicted subsequent infant word tokens (i.e., amount of language, coded following the Systematic Analysis of Language Transcripts [SALT]). Further, earlier infant Mean Length of Utterance (MLU; reflecting language complexity, also derived from SALT coding) predicted later caregiver MLU, even when controlling for variability in infant ages and clear within‐domain temporal stability/continuity in key measures (i.e., caregiver sensitive responsiveness and infant word tokens; and infant and caregiver MLU). These data add empirical support to theorization on how caregiver input can be both supportive of, and potentially influenced by, infant capacities, when infants have social‐communication differences and/or communication/language delays suggestive of possible emerging autism. Lay Summary: Although researchers think caregiver and infant behaviors both play a role in infant language development, most research has examined specifically how caregiver behaviors influence child language outcomes. Here, we investigated evidence for both caregiver‐to‐infant and infant‐to‐caregiver roles within 6‐min free‐play videos collected with 103 caregiver‐infant pairs seen at two assessments approximately 6 months apart. Infants were first seen around age 12 months following referral due to early signs of autism. We rated the free‐play videos for caregiver sensitive responsiveness and a range of aspects of caregiver and infant language, including number of words and language complexity. We found that caregiver sensitive responsiveness at around 12 months of infant age predicted the number of words infants used at around 18 months, and also that earlier infant language complexity predicted later caregiver language complexity. We ruled out that these links could simply be due to differences in infant ages and the natural tendency for these factors to show some stability over time. These data add evidence to theory about how caregivers can be both supportive of, and influenced by, their infants' own capacities, when infants have social‐communication differences and/or communication/language delays indicating possible emerging autism.